Metal-modified sludge-based biochar enhance catalytic capacity: Characteristics and mechanism. (15th April 2021) - Bao, Diandian; Li, Zhengwen; Tang, Rui; Wan, Chunli; Zhang, Chen; Tan, Xuejun; Liu, Xiang
Abstract: The improvement of the catalytic performance of sludge-based biochar plays an important role in the catalytic application of biochar. This work aimed to use transition metals and rare earth elements (Fe, Ce, La, Al, Ti) to modify sludge and prepare modified biochar with better catalytic performance through pyrolysis. Through the Fourier transform infrared spectrometer, Raman spectrometer, and X-ray photoelectron spectroscopy, the effects of different metal modifications on the surface morphology, molecular structure, element compositions, and valence of elements of biochar were comprehensively investigated. The results showed that metal elements were successfully modified onto the surface of biochar as metal oxides. Although the highest intensity of persistent free radicals was detected in blank-biochar by electron spin resonance, the intensities of hydroxyl radicals catalyzed by modified biochars in H2 O2 system were higher than that catalyzed by blank-biochar, indicating that the catalytic performance of modified biochar was mainly related to the metal oxide loaded and the defect structure on the surface of metal-modified biochar. Furthermore, in the H2 O2 system, the degradation efficiencies of tetracycline catalyzed by the biochars within 4 h were 51.7% (blank-biochar), 90.7% (Fe-biochar), 69.0% (Ce-biochar), 59.9% (La-biochar), 58.0% (Al-biochar), 58.0% (Ti-biochar), respectively, suggesting that Fe-biochar not only possessed the best catalytic performance but also shortened the reaction time. This research not only provided the possibility for recycling the waste activated sludge, but also proposed a modification method to improve the catalytic performance of biochar. Graphical abstract: Image 1 Highlights: Biochar was prepared by pyrolysis of metal-modified sludge. Metal elements were successfully modified onto the surface of biochar as metal oxides. The catalytic degradation efficiency of tetracycline by Fe-biochar was 90.7%. Fe-biochar can significantly accelerate the catalytic degradation reaction rate. Biochar catalytic ability depends on the defect structure and metal oxide contained.